2004
DOI: 10.1212/01.wnl.0000123696.98166.af
|View full text |Cite
|
Sign up to set email alerts
|

Limbic reductions of 5-HT 1A receptor binding in human temporal lobe epilepsy

Abstract: Patients with severe MTLE show reduced 5-HT1A receptor binding potential in the EEG-focus, and its limbic connections. [(11)C]WAY-100 635 PET may provide additional information to EEG, [18F]FDG PET, and MRI when evaluating patients with intractable seizures. Reductions in 5-HT1A binding in the insula and cingulate suggest a mechanism by which affective symptoms in MTLE may result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
88
4
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(109 citation statements)
references
References 33 publications
(34 reference statements)
8
88
4
6
Order By: Relevance
“…PET measurement of 5-HT 1A receptor binding in patients with mesial temporal lobe epilepsy has shown a significant reduction in the epileptogenic hippocampus and its limbic connections [12,29]. Serotonergic hypofunction demonstrated in human temporal lobe epilepsy is consistent with data from present study and from other labs using the KA seizure animal model [30].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…PET measurement of 5-HT 1A receptor binding in patients with mesial temporal lobe epilepsy has shown a significant reduction in the epileptogenic hippocampus and its limbic connections [12,29]. Serotonergic hypofunction demonstrated in human temporal lobe epilepsy is consistent with data from present study and from other labs using the KA seizure animal model [30].…”
Section: Discussionsupporting
confidence: 91%
“…Serotonergic hypofunction demonstrated in human temporal lobe epilepsy is consistent with data from present study and from other labs using the KA seizure animal model [30]. Together these data suggest a potential pathogenetic mechanism for depression in this patient population with high risk for affective disorder [12,31].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, Ott et al [11] found that children with complex partial seizures, including TLE and idiopathic generalized epilepsy of the absence type have had similar rates of depression. TLE and depression appear to share several mechanisms, including impairments in serotonergic, noradrenergic, glutamatergic and GABAergic transmission [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies showed a significant correlation between current depressive symptoms in TLE patients and reduced 5-HT 1A receptor binding in limbic regions including ipsilaterial hippocampus (19) and ipsilateral anterior cingulate cortex (47). These studies assessed only depressive symptoms, and did not consider whether TLE patients had met diagnostic criteria for a major depressive episode.…”
Section: Introductionmentioning
confidence: 99%